2015
DOI: 10.1093/trstmh/trv059
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of toxocariasis in preschool children in Aragua state, Venezuela

Abstract: The results from this work show the presence of infection and a high prevalence of antibodies against Toxocara spp. in the studied municipalities and indicate that toxocariasis poses a serious health problem to preschool children in Aragua state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
3
6
0
1
Order By: Relevance
“…more often than girls (64.8% in boys and 51.2% in girls). This trend was also observed in previous studies [11,22,23]; it has been hypothesized that boys engage in more outdoor activities than girls; thus, they are more likely to be in contact with soil and dogs. However, sex was not significantly associated with Toxocara seropositivity in either the univariate or multivariate analysis in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…more often than girls (64.8% in boys and 51.2% in girls). This trend was also observed in previous studies [11,22,23]; it has been hypothesized that boys engage in more outdoor activities than girls; thus, they are more likely to be in contact with soil and dogs. However, sex was not significantly associated with Toxocara seropositivity in either the univariate or multivariate analysis in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review and meta-analysis revealed that the global seroprevalence of toxocariasis was 19.0%, with the highest rate in the African region (37.7%) and the lowest rate in the Eastern Mediterranean region (8.2%) [20]. Many factors have been proposed to be involved, including contact with dogs [11,15], children's age [21], and male sex [11,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…more often than girls (64.8% in boys and 51.2% in girls). This trend was also observed in previous studies [8,18,19]; it has been hypothesized that boys engage in more outdoor activities than girls; thus, they are more likely to be in contact with soil and dogs. However, sex was not significantly associated with Toxocara seropositivity in either the univariate or multivariate analysis in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…In Western countries, the prevalence was 5.0% in the United States [14], 8.0% in Italy [15] and 16.0% in Greece [16]. Many factors have been proposed to be involved, including contact with dogs [8,12], children's age [17] and male sex [8,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Toxocariasis, a highly underrated and neglected disease, is caused by Toxocara canis and Toxocara cati, which are important intestinal nematodes of dogs and cats, respectively [1][2][3][4]. Of these, T. canis is the most common causative agent of human toxocariasis [5][6][7][8]. Humans acquire toxocariasis by accidental ingestion of embryonated T. canis eggs (from water or soil contaminated by infected cat/dog faeces) or encapsulated larvae (from raw/undercooked meat); toxocariasis usually does not show any symptoms [3,9,10].…”
Section: Introductionmentioning
confidence: 99%